1968
DOI: 10.1002/app.1968.070121204
|View full text |Cite
|
Sign up to set email alerts
|

Separation of liquid mixtures by using polymer membranes. I. Permeation of binary organic liquid mixtures through polyethylene

Abstract: synopsisThe permeation characteristics and the separation behavior of 25 combinations of binary liquid mixtures through low-density polyethylene membrane have been investigated. The organic compounds studied were members of the homologous series of liqiiid aliphatic hydrocarbons between n-pentane and n-nonane as well as some aromatic and cyclic compounds. A special permeation cell was designed in order to study permeation rates at different temperatures ranging from 25 to 45°C. The rate of permeation increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(42 citation statements)
references
References 7 publications
3
37
0
1
Order By: Relevance
“…Figures 13 and 14 show that over a wide temperature region, the experimental data closely obey the Arrhenius equation. If the experiment cell is improved so that it can work under pressure and as a result the operating temperatures of 90 and 95 wt % feed concentrations can be raised to 90°C, then, according to Figure 13, permeation fluxes will reach 621.5 (g/ m2 h ) and 354.6 ( g/m2 h ) respectively for 90 and 95 wt % feed concentrations, while, according to Figures 6,8, and 10, the separation factors should not change much. Arrhenius relationship between permeation flux and temperature.…”
Section: Optimization Of Pervaporation Runsmentioning
confidence: 98%
“…Figures 13 and 14 show that over a wide temperature region, the experimental data closely obey the Arrhenius equation. If the experiment cell is improved so that it can work under pressure and as a result the operating temperatures of 90 and 95 wt % feed concentrations can be raised to 90°C, then, according to Figure 13, permeation fluxes will reach 621.5 (g/ m2 h ) and 354.6 ( g/m2 h ) respectively for 90 and 95 wt % feed concentrations, while, according to Figures 6,8, and 10, the separation factors should not change much. Arrhenius relationship between permeation flux and temperature.…”
Section: Optimization Of Pervaporation Runsmentioning
confidence: 98%
“…Thus, the partition coefficient of the four polymer films is an exponential function of the composition of the mixture, which is in agreement with most of the experimental observations. 10,11,18 In addition, recent theoretical developments have shown that, in the case of the permeation of a binary mixture across an elastomer membrane, log(␣ AB ) expressed as a function of B0 is a straight line with the slope AB . 15,16 By transposing this theoretical result obtained on elastomer membranes to thermoplastic polymer films above their T g (one this assimilates crystals to reticulation points), which is the case at 60°C for each of the polymers considered here, it is possible to evaluate the Flory-Huggins interaction coefficient between methanol and toluene at 3.02 on average, which is an acceptable order of magnitude.…”
Section: Analysis Of the Partition Coefficient Of The Mixturementioning
confidence: 99%
“…The flux of either liquid by itself can be measured and it has been found that the concentration dependence of the flux is quite well accounted for in terms of the effect of the liquid on the free volume of the polymer phase1 [7][8][9][10][11][12][13][14][15][16][17][18][19] When two swelling liquids are present together they may affect one another's ability to swell the membrane and furthermore the thermodynamics of such a three component system including an amorphous polymer is highly complex. In particular, it seems certain that because each liquid contributes to the free volume of the polymer phase each will contribute a factor to the diffusion coefficient/concentration inter-relationship of the other.…”
Section: Pervaporationmentioning
confidence: 99%
“…The associated linear flux equations which have conjugated flows and forces arc = L11Ap + L12Ap2 (15) 02 = L21Ap1 + L22Au2 (16) Here the LIk are average coefficients across the membrane and depend not only on the nature of the membrane and the temperature but also on its thickness and the compositions of the solutions. Because Ap1 and A1i2 are connected through the Gibbs-Duhem equation, the flux equations (15) and (16) do not suggest convenient experiments for determining the LIk coefficients.…”
Section: Particle and Practical Permeability Coefficientsmentioning
confidence: 99%